Measuring Active Citizenship through the Development of a Composite Indicator - Hoskins, Bryony Louise; Mascherini, Massimiliano (Social indicators research, 2009)
This article defines Active Citizenship within a European context as a broad range of value based participation. It develops a framework for measuring this phenomenon which combines the four dimensions of Protest and Social Change, Community Life, Representative Democracy and Democratic values. The European Social Survey 2002 is used to populate the framework as this survey provided the best data coverage available and covered 19 European Countries. In total 61 indicators were selected. A composite indicator, The Active Citizenship Composite Indicator (ACCI), is built using the framework provided and using experts¿ weights. In addition, the robustness of the results is tested using sensitivity analysis. The limitations to the ACCI are explained in terms of the limitation of the data availability in particular concerning the new forms of participation and less organised forms of participation. Nevertheless, ACCI proved to be statistically robust and reliable and proved to be a useful tool for monitoring levels of citizenship in Europe. The results of Active Citizenship Composite Indicator exhibit interesting and quite distinct regional patterns. The results showed that the Nordic countries, and in particular Sweden, have the highest rate of Active Citizenship, followed by Central Europe and Anglo-Saxon countries. Mediterranean countries are next followed by Eastern European countries that close the ranking.
Keywords: jeunesse